Analisis tata letak ruang pada Toko Ritel Pelita dengan metode Activity Relationship Chart (ARC) dan Total Closeness Rating (TCR) - Salma, Siti; Khanifa, Sabila Silkha Milla; Ramadani, Zahra Afrina; Fahma, Me Raira; Firdaos, Firdaos (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Store layout plays an important role in optimizing the shopping experience and operational efficiency of stationery retail stores. This study aims to analyze the suitability of layouts in Pelita retail stores with the Activity Relationship Chart and Total Closeness Rating approaches. Data collection methods include primary and secondary data. Primary data is obtained through interviews and field observations, while secondary data is used to strengthen primary data. Linkages between store spaces facilitate employee operations and area access for customers, thus creating a comfortable shopping experience. The results of the Activity Relationship Chart and Total Closeness Rating analysis show that display shelves have the highest value of 174, which means the importance of product placement is easily accessible to customers. In addition, areas with high proximity relationships with display shelves, such as parking lots and cashiers are placed close together to facilitate customer access and speed up the shopping process.